Modified Limberg transposition flap in the treatment of pilonidal sinus disease - Kaya, B.; Eris, C.; Atalay, S.; Bat, O.; Bulut, N. E.; Mantoglu, B.; Karabulut, K. (Springer, 2012)
Pilonidal sinus disease (PSD) is a common problem in surgical practice. Different non-surgical and surgical methods have been used for treating PSD. Flap techniques including the Limberg flap have become more popular in recent years. A modified Limberg flap was used to reduce the problems of skin maceration and recurrence associated with the conventional Limberg flap technique. The aim of this retrospective study was to assess the effectiveness of the modified Limberg flap technique for PSD. Medical records of 94 patients with PSD who had been treated with a modified Limberg flap between December 2006 and 2009 were evaluated. The patients' age, sex, duration of preoperative symptoms, operative time, mean hospital stay, postoperative complications, wound infection rate, maceration rate and recurrence rate, time until return to work, time until sitting on the toilet without pain, hypoesthesia in the gluteal region, and satisfaction score were recorded during follow-up or at the last interview. Clinical data were obtained at the end of the 5th postoperative day and at 1, 3, 6, and 12 months following surgery. There were 83 male and 11 female patients. The mean operative time was 38.95 +/- A 6.77 min (range 30-67 min). All patients were followed up longer than 12 months, and the mean follow-up period was 30.97 +/- A 12.7 months (range 12-54 months). While wound dehiscence was observed in only one patient, we did not detect any case of flap necrosis. Two cases of seroma were observed. Wound infection was detected in 5 patients (5.3%). Surgical drainage was performed in 2 cases. Another 3 patients were treated with oral antibiotics. Maceration of the surgical incision site was detected in 8 patients (8.5%) who were all successfully treated with conservative measures. There were 4 patients (4.2%) with recurrence in this series. When compared with the available data on use of the conventional Limberg flap for PSD, our results suggest that use of the modified Limberg flap is associated with a lower maceration and recurrence rate, and greater patient satisfaction.
Keywords: Pilonidal sinus; Limberg flap